Dental periodontitis (Texas Journal of Medical Science, 2021)
Periodontitis is an inflammation of the tissues surrounding the tooth (periodontium) with the subsequent destruction of the ligaments of the tooth with the bone tissue of the jaw. It is manifested by bleeding and inflammation of the gums, pain when pressing, unpleasant odor from the mouth, tooth mobility. Further development of periodontitis leads to the formation of periodontal pockets, suppuration, loosening and loss of teeth. It can be complicated by abscesses and fistulas on the gums, periostitis and lymphadenitis. The following article looks into the illnes named pariadontisis and its causes and symptoms.